2023
DOI: 10.1111/1348-0421.13067
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of CXCL10 for the occurrence of immune‐related adverse events in patient with renal cell carcinoma

Abstract: Immune checkpoint inhibitors (ICIs) have recently improved the prognosis of various cancers. By contrast, some immune-related adverse events (irAEs) caused by ICIs are fatal and have become problematic. The pathogenesis of irAEs remains unknown and must be elucidated to establish biomarkers. This study investigated plasma cytokine, chemokine, and anti-CD74 autoantibody levels in patients with renal cell carcinoma (RCC) and analyzed their association with irAEs. In a discovery cohort of 13 patients, plasma leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Furthermore, CD74 protein was expressed at much higher levels in the lungs of patients with ICB-induced pneumonitis compared to normal lung tissue, suggesting that the high expression of CD74 autoantibodies may have relevance in the mechanism of ICB-induced pneumonitis [93]. A follow-up study investigated CD74 autoantibody levels in the plasma of Japanese patients with renal cell carcinoma receiving ICB combination or monotherapy; in this work, CD74 autoantibody levels did not represent a predictive biomarker of pneumonitis irAE or higher-grade irAEs [94]. These conflicting reports suggest that further work is needed to establish whether CD74 can be a useful biomarker for irAE development.…”
Section: Mif and Cd74 As Putative Predictive Biomarkers Of Irae Devel...mentioning
confidence: 92%
“…Furthermore, CD74 protein was expressed at much higher levels in the lungs of patients with ICB-induced pneumonitis compared to normal lung tissue, suggesting that the high expression of CD74 autoantibodies may have relevance in the mechanism of ICB-induced pneumonitis [93]. A follow-up study investigated CD74 autoantibody levels in the plasma of Japanese patients with renal cell carcinoma receiving ICB combination or monotherapy; in this work, CD74 autoantibody levels did not represent a predictive biomarker of pneumonitis irAE or higher-grade irAEs [94]. These conflicting reports suggest that further work is needed to establish whether CD74 can be a useful biomarker for irAE development.…”
Section: Mif and Cd74 As Putative Predictive Biomarkers Of Irae Devel...mentioning
confidence: 92%
“…In two studies, elevated pretreatment levels of anti-CD74 and IL17 were found to be associated with pneumonitis in patients with solid tumors who received anti-PD1 with or without anti-CTLA-4 ICIs. However, another study by Miura et al did not find this association [ 64 , 106 , 109 ].…”
Section: Biomarkersmentioning
confidence: 97%
“…No association [15] ↓ risk [118] Pulmonary Pneumonitis Absolute eosinophil count ≥125 ↑ risk [119] White blood cell count ↑ risk [120] Absolute neutrophil count ↓ risk [120] Neutrophil-lymphocyte ratio No association [120], ↓ risk [100] Low IFN-γ ↑ risk [121] IL17 and anti-CD74 levels Conflicting results: ↑ risk [106,109] Not associated [64] HLA-B35 and HLA-DRB1*11 haplotype ↑ risk [122] HLA-B*35:01 ↑ risk [34] Table 3. Cont.…”
Section: Organ System Biomarker Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…within the cancer microenvironment (7,8). In kidney cancer cases, elevated serum levels of CXCL10 have been associated with an increased incidence of immune-related adverse events triggered by immune checkpoint inhibitors (9)(10)(11). CXCL10's pivotal role extends to mediating inflammation, guiding immune cells to sites of infection or injury.…”
mentioning
confidence: 99%